Rectal diclofenac; an effective modality for pain relief after vaginal birth - Rabia Nafees; Zahra Safdar; Faiqa Saleem Baig; Sumera Zaib; Aisha Iftikhar (BioMedica, 2022)
Background and Objective: Vaginal delivery (VD) is the safest delivery option for the mother and is associated with quick recovery and minimal maternal morbidity and mortality. However, one of the commonest fears among women about VD is pain. This study aims to assess the effectiveness of diclofenac suppositories (per rectum) compared to the intramuscular diclofenac for the pain relief in females after VD. Methods: This prospective comparative was study conducted at the Emergency Section (labor room) of Obstetrics & Gynecology Department in one of the tertiary care teaching hospitals of Lahore, Pakistan. A total of 182 female patients undergoing VD were selected and further divided into group A and group B. Group A was administered rectal analgesia in the form of rectal suppositories (100 mg) immediately after perineal tear (first and second degree only) repair and repeated after 6 hours. While group B received one injection of intramuscular diclofenac, immediately after perineal tear repair. The pain score was measured on a graphical score using Graphic Rating Scale, immediately at rest, during movement, and during urination. The pain score was reassessed after 6 hours with the same parameters and compared between both groups. Results: The overall pain score was significantly lower immediately (p = 0.004) and 6 hours (p = 0.002) after VD in group A at rest, during movement, and during urination as compared to group B. Conclusion: The use of rectal diclofenac suppositories is a simpler and more effective and acceptable method of reducing the pain experienced by the women following perineal trauma after vaginal childbirth.